2006
DOI: 10.1007/s00428-006-0286-2
|View full text |Cite
|
Sign up to set email alerts
|

Liver glycogen bodies: ground-glass hepatocytes in transplanted patients

Abstract: Ground-glass hepatocytes have been described in Lafora's disease, fibrinogen deposition, hepatitis B, type IV glycogenosis, and alcohol aversion (cyanamide) therapy. We encountered ground-glass hepatocytes with intracytoplasmic inclusions in four liver biopsies from three transplanted patients who had none of the above-mentioned underlying diseases. One patient was a 4-year-old boy who had a kidney transplant for severe ureterovesical reflux. Patient 2 was a 52-year-old man who had two liver transplants becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Two unusual manifestations associated with GVHD involve hepatocyte inclusions recognized by periodic acid Schiff (PAS) staining. These include both diastase-sensitive polyglucosan-like ground-glass cytoplasmic inclusions [35, 36] and PAS-positive diastase-resistant pseudo-Lafora bodies thought to represent an unusual form of degenerative organelles and glycogen [37, 38]. Data are insufficient to determine whether IHC staining for replicative senescence by p21 [39], determination of the Th17/T regulatory cell ratio [40], or staining for C4d provides additional information above and beyond the usual histological evaluation [41].…”
Section: Histological Criteria For the Diagnosis Of Gvhdmentioning
confidence: 99%
“…Two unusual manifestations associated with GVHD involve hepatocyte inclusions recognized by periodic acid Schiff (PAS) staining. These include both diastase-sensitive polyglucosan-like ground-glass cytoplasmic inclusions [35, 36] and PAS-positive diastase-resistant pseudo-Lafora bodies thought to represent an unusual form of degenerative organelles and glycogen [37, 38]. Data are insufficient to determine whether IHC staining for replicative senescence by p21 [39], determination of the Th17/T regulatory cell ratio [40], or staining for C4d provides additional information above and beyond the usual histological evaluation [41].…”
Section: Histological Criteria For the Diagnosis Of Gvhdmentioning
confidence: 99%
“…In our patient, the HCV viral load increased significantly after transplant, but did not have inflammatory changes consistent with reactivated HCV infection in liver biopsy. We concluded that our patient’s hepatic dysfunction was due to tacrolimus toxicity because of the following: (i) extensive hepatic work‐up that exclude all other etiologies including hepatic veno‐occlusive disease, (ii) the ground glass hepatocytes found on transjugular liver biopsy [9], and c) the rapid reversal of LFT after tacrolimus was stopped. Ground‐glass hepatocytes have been described earlier with other causes, such as chronic hepatitis B infection, Lafora’s disease, type 4 glycogenosis, cynamide alcohol aversion therapy, and fibrinogen storage disease.…”
mentioning
confidence: 99%
“…Ground‐glass hepatocytes have been described earlier with other causes, such as chronic hepatitis B infection, Lafora’s disease, type 4 glycogenosis, cynamide alcohol aversion therapy, and fibrinogen storage disease. There has been report of patients with glycogen inclusions in hepatocytes in patients on multiple immunosuppressive medications, which included tacrolimus [7–10].…”
mentioning
confidence: 99%
“…All of the 12 patients were using polypharmacotherapy, mostly including steroids and tacrolimus (FK506) (4). Similarly, all three patients in the series by Bejarano et al were undergoing multidrug medication including steroids and tacrolimus (9). In summary of the above studies, PAS+ ground glass inclusions have been mostly reported in immunosuppressed patients on multidrug medications in a setting of transplantation and immunosuppression.…”
Section: Discussionmentioning
confidence: 90%